Llenado de un recipiente: modelación y simulación de conceptos básicos afines a la ingeniería (2020)
The behavior of a container filled with two fluids, honey and lubricant, is characterized. Initially, we will describe the variables qualitatively and proceed to experimentation recording the measurements. Subsequently, the data analysis is performed and through the characterization of the variables the relationships between the parameters are determined, and a model adjusted to the results obtained is constructed. From the experimentation, and according to the model associated with it, the simulation of the event is constructed through Geogebra, and the process is repeated with each of the transformations of the event for its analysis and comparison. The results can be used as an ideal educational tool for the integration of areas of basic knowledge relatedto engineering.